ISU GLOBAL MANAJEMEN PEMBIAYAAN PENDIDIKAN DI SD INDONESIAN CREATIVE SCHOOL PEKANBARU - Rahmadoni, Jefril (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2018)
This study purposed to find out how finance management in one of the international-based schools in the development of global issues of education today is useful to improve the quality of education in Indonesia. This research was qualitative, where in this paper I saw the strategies used by school in running the management of educational finance. Data collection techniques in this study were interviews with principals, vice principals, treasurers, and the results of financial observations in the Primary School of Indonesian Creative School Pekanbaru. The results showed that the management of educational finance had been done well 1) the process of budgeting according to the procedure; 2) sources of finance obtained from several sources of funds; 3) the constraining factor in the management of educational finance belongs to the flow of disbursement of funds long enough; 4) supervision and accountability in the educational finance is going well; and 5) Foundations, principals, vice principals, treasurers, school committees, teachers and UPTD Education involved in the education finance management process.